A quantitative method to determine preservice chemistry teachers' perceptions of chemical representations. Issue 4 (15th August 2017) - Head, M. L.; Yoder, K.; Genton, E.; Sumperl, J.
Abstract : Chemical representations serve as a cornerstone to guide the teaching of chemistry concepts. The influence that a chemical representation has on instruction is largely dependent on how well the viewer interprets the information in the representation. Teachers serve as a guide to the students as they point out and make connections between the features present in a chemical representation. To influence how well the teacher serves as a guide it is important to develop teachers' pedagogical content knowledge as it relates to visualizations. As a first step towards developing this area of teaching expertise it is crucial to develop an understanding of how preservice chemistry teachers perceive a variety of chemical representations. To this end, this paper presents a novel card-sorting methodology that utilizes Johnstone's triangle as a continuum to determine how chemistry preservice teachers perceive representations relative to the presence of each of the three representational levels: macroscopic, submicroscopic, and symbolic. This study has determined that this methodology is both valid and reliable among a group of chemistry preservice teachers. The participants were able to effectively detect the presence or absence of the macroscopic domain. However, there was greater variance when the symbolic and submicroscopic levels were present. In addition, variance among the participants' responses also increased dramatically when multiple levels were present in one representation. This was largely a result of what key features the participant focused on while viewing the card. The variance results of this study, along with the accompanying rationales for the placement of the cards, serve to inform the development of practices to further foster preservice chemistry teachers' pedagogical-visual-content-knowledge (PVCK).